Dorsal Arachnoid Web: A Rare Cause of Myelopathy. Issue 1 (30th December 2021) - Buttiens, Arvy; Feyen, Bart; Dekeyzer, Sven
Teaching point: The scalpel sign is pathognomonic for a dorsal arachnoid web, a rare clinical-radiologic entity that can cause myelopathy.